Proses Pengalihan Cessie Dan Dampaknya Terhadap Hak Debitur Dalam Perjanjian Kredit Perbankan - Sasmita, Baiq Supiya Indah (LPPM Universitas Ekasakti Padang, 2024)
This study aims to determine the process of transferring the cession carried out by PT. Bank Tabungan Negara, Jember branch and PT. Bank Tabungan Negara, Banyuwangi branch in the Credit Agreement Has Complied with the Governing Legal Provisions and to determine the legal impact of the application of the cession clause on the rights of debtors in decision Number 1327 K / Pdt / 2021. The research method used in this study is the doctrinal research method. Based on this study, it is concluded that credit agreements in Indonesian civil law, although not specifically regulated in Book III of the Civil Code, still follow general legal principles such as the principle of freedom of contract. And the application of the cession clause in the credit agreement has an important impact on the rights of debtors in terms of transparency, justice, legal certainty, protection of debtor rights, and the continuity of legal relations.